Decentralizing Payments for Hydrological Services Programs in Veracruz, Mexico: Challenges and Implications for Long-term Sustainability. Issue 12 (2nd December 2018) - Nava-López, Mariana; Selfa, Theresa L.; Cordoba, Diana; Pischke, Erin C.; Torrez, David; Ávila-Foucat, Sophie; Halvorsen, Kathleen E.; Maganda, Carmen
Abstract: In this policy review, we analyze two payments for hydrological services matching programs operating in the Antigua water basin in the state of Veracruz, Mexico. Mexico's Matching Program was created to transition from the national payments for hydrological services program to programs that would be financed by local governments, local water users and the private sector. Based on the analysis of organizational documents and key informant interviews with institutional actors, we describe the distinctive origins and organizational structures of these two programs, and how these differences have led to unique challenges for each program. We conclude that payments for ecosystem services programs that incorporate community-level organization and extensive technical assistance, along with expanded direct payments from ecosystem service users, have the greatest potential for achieving long-term sustainability.